Chinese FDI in Vietnam under Xi Jinping’s policy in the 21st century - Pittaya Suvakunta (Journal of Frontier in Economic and Management Research, 2026)
This research study, entitled as “Chinese FDI in Vietnam under Xi Jinping’s Policy in the 21st Century”, aims (1) to study Chinese FDI in Vietnam under Xi Jinping’s policy, and (2) to study the factors of Chinese FDI in Vietnam and the change on geo-economics. The strategy of Chinese FDI in Vietnam under Xi Jinping’s policy in the 21st century is a result of President Xi Jinping's announcement of the Belt and Road Initiative (BRI). The strategy has evolved into partial cooperation between China and Vietnam, which is shaped by China's economic relations strategy with ASEAN. This extent will be a crucial driving force for China’s investment in Vietnam. Moreover, Vietnam has a high potential as a groundwork for investment, production, and export to other foreign countries. Since the factors of Chinese FDI in Vietnam and the change on geo-economics are involved with politics and economics, they have an impact on China's investment in Vietnam. The political factor has risen due to the policy of President Xi Jinping regarding the declaration of the BRI. Economic factor concerns the opening of new markets, the release of domestic supply, and the adjustment of international reserve funds by establishing the Asian Infrastructure Investment Bank (AIIB). Meanwhile, China's open strategy towards foreign countries has brought its strategic investment policies in Vietnam closer together, as well as the economic interests of both countries. This may lead to a significant impact on economic and political relations between China and Vietnam in the future.